The changing incidence of human hydatid disease in England and Wales. - Palmer, S. R. (Cambridge University Press, 1987)
The incidence of hospital-diagnosed human hydatid disease acquired in the UK was estimated from a survey based on Hospital Activity Analysis data for the period 1974-83. The average annual incidence in Wales was 0.4 per 100,000 population compared with 0.02 per 100,000 in England. Within Wales, Powys, and particularly Brecknock, had the highest incidence (7 per 100,000 per year). Compared with the period 1953-62, the average annual incidence for Wales fell by half (from 0.8 to 0.4 per 100,000 per year), but in Powys the incidence did not decline, and in Brecknock and Montgomery there was a marginal increase. In comparison with 1953-62, the age-specific incidence in Wales and Powys decreased in each age group with the notable exception of children less than 15 years of age. This finding emphasizes that transmission of Echinococcus granulosus to humans is still occurring at hyper-endemic levels in parts of England and Wales and that control efforts should be intensified.